Control Design of Automatic Inflatable Vest for Deep Pressure Therapy - Husaini, Farhan; Maula, Mohammad; Ammarullah, Muhammad; Afif, Ilham; Lamura, M Danny; Winarni, Tri Indah; Jamari, J (Departemen Teknik Mesin, Fakultas Teknik, Universitas Diponegoro, 2024)
This research focuses on enhancing the control system of the commercial inflatable vest to optimize pressure regulation for deep pressure therapy (DPT) in children with autism spectrum disorder (ASD). The main goal is to provide a safe and reliable DPT experience with calming effects. The proposed control system incorporates a feedback loop mechanism to maintain the desired pressure level and includes safety features to prevent overinflation. The study dis-cusses the development of the pressure control system, covering both hardware and software components. Experimental results demonstrate the system's effectiveness in maintaining the target pressure with the average error is 1.531%. This study has successfully advanced deep pressure therapy devices, emphasizing the significance of automatic pressure control that meets the criteria for medical gas pressure (error no greater than 5%) and incorporates safety features as a therapy device.